“Redes sociais de resistência”: o relato da rede social cooperativa e agroecológica da comuna da terra - Filus , Veridiany (2022)
This thesis analyzes the development and context of controversies regarding the dynamics of production flow at Cooperativa Comuna da Terra, located in Mario Lago Settlement in Ribeirão Preto, State of São Paulo. As to theoretical and methodological foundations, It relies on the Actor-Network Theory (ANT) as specifically described in ‘Reassembling the Social: An Introduction to ActorNetwork-Theory’, published by Bruno Latour in 2005 and translated into Portuguese in 2012.The thesis is composed of four papers. The structure of the thesis is divided into four articles, and the proposal has agroecology, the cooperative movement and the relationship with consumers as its guiding principles. Understanding the place as a grouping of associations, which include numerous non-social entities that become participants in the sharing of a common world, called collective. This movement identified the fundamental importance of describing and dialoguing about the existence of the relationship between humans and non-humans within networks, as well as interventions to improve and strengthen this relationship.